Destined to Lead a Lot of Men in a Desperate Battle: Hollywood’s Take on Contradictory Military Commanders in Patton (1970) and Alexander (2004). - Taneli Hiltunen (Finland, 2022)
The research questions of this article are as follows: How are General Patton and Alexander the Great represented as military commanders in the films Patton (1970) and Alexander (2004)? Why are famous soldiers such an enduring topic of historical biopics – despite a plethora of contemporary, extremely brutal conflicts? Do the films in question manage to convey their grand strategic vision? To what degree is the forceful public persona counterbalanced with serious character flaws, weaknesses and mysticism? I will concentrate on four especially crucial facets of Patton and Alexander that affect our reading of the title characters’ nature, namely the depictions of strategic and tactical abilities, speech giving, militaristic attitude, and religiosity. Speeches and different shades of militarism are fairly typical aspects of soldier biopics of any given decade, but meticulous attention paid to tactical details and religious beliefs is actually something quite rare. The scenes I have chosen for closer scrutiny help to define the screen Patton and Alexander primarily as commanders but also as thinking individuals.
The thematic richness and complexity of Patton and Alexander is quite uncommon among the big-studio-backed Hollywood epics, and the directors and screenwriters have taken considerable risks in portraying the title characters not only as heroic and inspirational but at times in a very harsh and unflattering light. While the two films can be said to partly strengthen the larger-than-life legend, they still contain enough moments of criticism to warrant a credible, multilayered characterisation instead of simplistic hero worship. The representations of Patton and Alexander do not hide away their seemingly inherent militarism, and although it is fairly easy to see the filmmakers’ respect towards their protagonists, there are no clear signs of condoning acts of despotism, e. g. Patton slapping and madly yelling at an upset corporal and calling him ’a yellow bastard’, and Alexander violently persuading his men to march on at the Hyphasis River. The two are walking contradictions as likely to attain greatness and wide admiration for their martial prowess as to gravely insult and destroy the very men they so deeply respect.
And yet, both Alexander the Great and George S. Patton Jr. emerge as undeniably extraordinary individuals, no matter how much weight one puts to their very significant character flaws. They could be simultaneously described as heroes and anti-heroes – the exact type of character that usually keeps modern audiences and critics (why not researchers as well) fascinated.